ENCOURAGING CRITICAL THINKING (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article explores the vital role of critical thinking in education and personal development, highlighting its importance in an increasingly complex and information-rich world. It examines strategies for cultivating critical thinking skills among learners, such as fostering an environment of inquiry, encouraging questioning and reflection, and promoting open discussions. The article also emphasizes the benefits of critical thinking, including enhanced problem-solving abilities, improved decision-making, and greater creativity. By equipping individuals with the capacity to analyze and evaluate information critically, we prepare them to engage thoughtfully with diverse perspectives and make informed choices in their personal and professional lives. Ultimately, this article serves as a call to action for educators, parents, and leaders to prioritize critical thinking as a cornerstone of effective learning and societal engagement.